Comprehensive evaluation of immunomodulation by moderate hypoxia in S. agalactiae vaccinated Nile tilapia. Issue 66 (July 2017) - Gallage, Sanchala; Katagiri, Takayuki; Endo, Masato; Maita, Masashi
Abstract: Streptococcus agalactiae is a major bacterial pathogen in tilapia aquaculture. Vaccines are known to provide protection but S. agalactiae clearance in tilapia can be reduced by marginal environmental conditions. Therefore, the purpose of this study is to examine S. agalactiae clearance in vaccinated Nile tilapia under moderate hypoxic (55± 5% DO) and normoxic (85 ± 5%DO) conditions. Fish were acclimatized to either moderate hypoxia or normoxia and immunized with formalin-inactivated S. agalactiae . Fish were experimentally challenged with S. agalactiae at 30 days post-vaccination. Serum antibody titer was significantly higher in vaccinated fish kept under normoxic condition compared to the moderate hypoxic condition at fifteen and thirty days post-vaccination. The cumulative mortality following challenge was significantly reduced in vaccinated fish kept under normoxic condition compared to those in moderate hypoxic condition reflecting that pre-challenge antibody titer may correlate with survival of fish. Blood and tissue pathogen burden detection of S. agalactiae studies revealed that culturable S. agalactiae cells could not be detected in the blood of normoxic vaccinated fish at all the sampling points. In contrast, fish vaccinated in moderate hypoxic condition had considerable number of culturable S. agalactiae cells in their blood up to 5 days following challenge. Phagocytosis and intracellular reactive oxygen species (ROS) production were lowered by moderate hypoxia in vitro . Furthermore, presence of specific antibodies and higher specific antibody level in the serum increased phagocytosis, ROS production and lowered intracellular survival of S. agalactiae in head kidney leukocytes. Overall this study has highlighted that S. agalactiae clearance in vaccinated Nile tilapia is modulated by moderate hypoxia. One of the possible explanations for this might be less efficient phagocytic activities due to low oxygen availability and lower specific antibody production in vaccinated fish. Highlights: Moderate hypoxia lowered antibody production in Nile tilapia against S. agalactiae. Cumulative mortality was higher in vaccinated fish under moderate hypoxic condition. Blood and brain bacteria burden was lowest in normoxic vaccinated fish. Phagocytosis and ROS productions enhanced by specific antibodies in opsonising serum.